Pengaturan Pendampingan Narapidana yang Menderita Gangguan Mental selama Menempuh Hukuman di Lapas - Siti Aisyah (LPPM Universitas Terbuka, 2023)
Psychiatric disorders can occur at will in correctional institutions because their freedom is limited and interaction with people outside the institution is not possible. Limited freedom and minimal social interaction in correctional institutions can interfere with the mental health conditions of those who are already vulnerable. This condition can cause stress which leads to depression and mental disorders, which in turn can cause a person to go crazy. Therefore, appropriate arrangements and coaching are needed to provide the necessary care and support for dealing with those with psychiatric disorders. In this study, researchers used a normative research approach by examining law no. 22 of 2022 concerning correctional and analyzed this article deductively by referring to the literature in literature review. The purpose of this study is to analyze efforts to arrange assistance for revocation for those who experience psychiatric disorders while serving time at the Class IA Penitentiary in Surabaya, how to recover from losing their minds (crazy) while in prison, what is the legal status of someone who has been an asylum but has been recovered from psychiatric disorders and obstacles or obstacles when carrying out coaching for sufferers who are insane (mental disorders).